Air-stable and highly luminescent bismuth complex nanoparticles. Issue 22 (29th April 2016) - Zhou, Dan-Dan; Liu, Bo-Mei; Zhou, Yang; Chen, Mu-Zi; Fang, Yong-Zheng; Hou, Jing-Shan; Li, Li-Na; Sun, Hong-Tao
Abstract : We report, for the first time, the preparation of air-stable, solution-processed, luminescent Bi complex nanoparticles (NPs) through a one-pot wet chemical reaction method. Abstract : We report, for the first time, the preparation of air-stable, solution-processed, luminescent Bi complex nanoparticles (NPs) through a one-pot wet chemical reaction method. Strong visible photoluminescence (PL) from these Bi complex NPs, with a quantum yield as high as 5.9%, can be achieved. Interestingly, the observed PL is distinctly different from other materials containing Bi. Based on detailed analyses, a multi-stage formation and growth process for the Bi complex NPs has been proposed, and the observed PL is attributed to the intrinsic electronic transition inherent to the whole NPs. This work not only provides a synthetic method for luminescent NPs with sizes larger than 2 nm, but also can contribute significantly to a better understanding of the photophysical behaviors of materials containing the Bi element.